2017 IEEE World Haptics Conference (WHC) 2017
DOI: 10.1109/whc.2017.7989955
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of air to ultrasonic friction reduction

Abstract: The origin of friction reduction on an ultrasonically vibrating plate has been the subject of debate. Recent work suggests that friction may be reduced due to intermittent contact caused by bouncing upon the vibrating surface [8], leaving the question of whether other phenomena such as levitation on a squeeze film of air also play a role. To probe the contribution of squeeze film levitation, we investigated the dependence of the friction reduction effect upon air pressure. An artificial finger was placed insid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…There are two primary strategies to actively modulate the friction forces felt on a surface: ultrasonic vibration and electroadhesion. Ultrasonic vibrations lower the friction between skin and a surface through a combination of reducing the total contact area and increasing the lubricating effect of air at the interface. Electroadhesion raises the friction felt using the capacitive force between skin and the surface to draw the skin toward the interface and increase the surface area. , Although both are generally compatible with existing smart screen technologies, several engineering challenges in ultrasonic vibration schemessuch as mechanically moving parts, the inability to implement multi-finger haptics, relatively high power consumption, and limited variability in the friction coefficienthave motivated researchers to explore and improve electroadhesion devices.…”
Section: Introductionmentioning
confidence: 99%
“…There are two primary strategies to actively modulate the friction forces felt on a surface: ultrasonic vibration and electroadhesion. Ultrasonic vibrations lower the friction between skin and a surface through a combination of reducing the total contact area and increasing the lubricating effect of air at the interface. Electroadhesion raises the friction felt using the capacitive force between skin and the surface to draw the skin toward the interface and increase the surface area. , Although both are generally compatible with existing smart screen technologies, several engineering challenges in ultrasonic vibration schemessuch as mechanically moving parts, the inability to implement multi-finger haptics, relatively high power consumption, and limited variability in the friction coefficienthave motivated researchers to explore and improve electroadhesion devices.…”
Section: Introductionmentioning
confidence: 99%
“…This overpressure causes the two objects to separate, as shown in Fig. 1(b), resulting in a controllable coefficient of friction-a phenomenon known as ultrasonic friction modulation or ultrasonic lubrication [9], [10]. The amount of separation is monotonically correlated to the vibration amplitude, enabling precise and controllable active lubrication at the interface [9].…”
Section: Working Principle and Design Ultrasonic Lubricationmentioning
confidence: 99%

Toward 

Atalla,
Tuijp,
Wiertlewski
et al. 2024
Preprint
“…An alternative to squeeze-film theory argues that the skin bounces on the plate, making intermittent contact of short duration, resulting in a reduction in the overall friction [20], [21]. Recent investigations under reduced pressure showed that air is nonetheless a critical factor in the modulation of friction [16], [22].…”
Section: Ultrasonic Friction Reduction Theoriesmentioning
confidence: 99%
“…In addition to levitation, the skin is forced into oscillation by the plate. During each oscillation, the gap closes, creating a cushion of air on which the tissues bounce [16]. Kaci et al derived a method to estimate the acoustic force applied to the skin during the harmonic oscillation produced by piezoelectric actuators.…”
Section: Introductionmentioning
confidence: 99%